Deprivation of liberty safeguards: how prepared are we?. Issue 3 (8th March 2010) - Lepping, Peter; Sambhi, Rajvinder Singh; Williams-Jones, Karen
Abstract : The Mental Health Act 2007 introduced Deprivation of Liberty safeguards into the Mental Capacity Act 2005 with potentially far reaching resource implications. There appears to be no scientific data regarding the prevalence of deprivation of liberty in clinical settings such as hospitals and nursing homes. We examined how many patients across a whole Trust area in Wales were subject to some lack of capacity, how well documented this was and how many were potentially deprived of their liberty. We found that no patient was deprived of their liberty, but 8% lacked capacity to make either basic or complex decisions; another 5% lacked capacity to make complex decisions. Documentation was good in mental health and community directorates, but there were gaps in documentation (not practice) in the medical and surgical directorates. Routine collection of data improved documentation regarding deprivation of liberty criteria. There is a high likelihood that senior nursing staff underestimate the number of patients who lack capacity.